An observational analysis to evaluate the influence of occlusion on body posture and plantar pressure - An in vivo study - Aishwarya Deshmukh; Shwetha Kumari Poovani; Prafulla Thumati (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of this study is to evaluate the influence of occlusion on body posture and plantar arch pressure. Settings and Design: An Observational analysis to Analyze the Influence of Occlusion on Plantar Pressure and Body Posture. Materials and Methods: A total of 30 asymptomatic subjects were selected for the study including 18 females and 12 males from age group 22 years to 28 years with a mean age of 24.83 years. Each subject underwent evaluation of occlusion at MIP using a Digital Occlusal analyzer (T-Scan III). At this point, the subjects were made to stand on a mat scan which consisted of a large postural platform sensor and a computer that displayed the plantar pressure data. The computer connected to the T Scan displayed the occlusal pressure analysis. This was followed by an evaluation of body posture using a posture grid where the photographs were taken and an evaluation of the frontal and lateral photos was done using the APECS - posture analysis app. Statistical Analysis Used: Statistical package for social sciences (SPSS) for windows version 22.0 Released 2013, Armonk, N Y: IBM Corp., was used to perform Statistical Analysis. A chi-square test was applied for qualitative variables to find the association. Paired t-test was applied to compare the changes in the quantitative parameters in eye-open and eye-closed conditions. The level of significance was set at 5%. Results: As observed from the results, occlusion for 40% of the subjects, where n = 12, was dominant on the right side. Occlusion for 23.3% of subjects, where n = 7, was dominant on the left side. Whereas, for 36.7% of subjects, where n = 11, the pressure distribution was almost equal on both sides. The inclination of body posture for 23.3% of subjects, where n = 7, was towards the right side. The inclination of body posture for 50% of subjects, where n = 11, was towards the left side. And, the inclination of body posture for 26.7% of subjects, where n = 8, was neutral i.e., balanced on the right and left side. Plantar pressure for 6.7% of subjects, where n = 2, was dominant on the right side. Plantar pressure for 36.7% of subjects, where n = 11, was dominant on the left side. Whereas, for 56.7% of subjects, where n = 17, the plantar pressure distribution was almost equal on both sides. Conclusion: On correlating the three parameters, it was found that occlusion for most of the subjects dominated on the right side, while body posture and plantar pressure dominated on the contralateral i.e., left side.